A Review on Manufacturing of Tablets by Using Various Granulation Techniques - Girish Pai Kulyadi (Journal of Global Pharma Technology, 2017)
Tablets are unit, compressed solid dosage form containing an Active Pharmaceutical Ingredient (API) with or without excipients. Tablets are manufactured by using different techniques such as wet granulation, dry granulation, and direct compression. Granulation is the procedure in which particles are held together with the help of linkages between the excipient and API. These links between the excipients and the API are developed both by compression and by employing various types of binding agents. Alternate approach includes using newer directly compressible (DC) grade excipients to prepare stable tablets. The present article mainly focuses on the different granulation techniques used for manufacturing of tablet and their advantages, disadvantages, and limitations and focuses on the technique to be selected for development of a good tablet.Keywords: Tablets, API, Direct compression, Dry granulation, Wet granulation, DC grade and Technique selection.